EVALUATION OF BROILER PERFORMANCE BY USING DIFFERENT ENERGY SOURCES (Indian Journal of Animal Production and Management, 2014)
The 400 straight run, day old Vencobb broilers chicks were randomly divided into four treatment groups of 100 birds each viz., control, T1, T2 and T3. Each group was further divided into two replications of 50 birds each. Four iso-caloric and iso-proteinous experimental rations were formulated by replacing maize with jowar, bajra and broken rice at 25 %. The control group having diet with 100 % maize. The soyabean meal was the sole protein source for all the four rations (control, T1, T2 and T3). The observations of the parameters were taken on weekly basis and were analysed by using Completely Randomized Design (CRD) and simple arithmetic calculations. The use of different energy sources i.e. jowar, bajra and broken rice can be very well replaced with maize in broiler ration without affecting the performance of the broiler.
Keywords: Energy sources; feed consumption; weight gain; FCR; broilers